GÉNERO Y MULTICULTURALIDAD: UN ENCUENTRO OBLIGADO. RETOS Y PERSPECTIVAS PARA LA INVESTIGACIÓN - Cordero, Teresita (Universidad de Costa Rica, 2013)
In the beginning of this essay, the author presents the contradiction between the discourse of human rights and the conditions of life of populations, in the environment of a capitalist system that fails to respond to the ideal of society sponsored by the world’s states. This is used to place the premise of diversity in the framework of inequality and forms of social discrimination such as racism, sexism andclassism. Some breakthroughs, that come from the feminist movement and provide insights for research from the subject of multiculturalism, are also reviewed here. As a general conclusion, the author points out the contributions from a critical perspective of power relations integrated with a situated conception of research, which in turn points to the specific problems, needs and demands of women in particular.